Simplified seismic assessment of buildings using non-uniform Timoshenko beam model in low-to-moderate seismicity regions. (1st August 2016) - Su, R.K.L.; Tang, T.O.; Liu, K.C.
Highlights: Preliminary seismic assessment is proposed for low-to-moderate seismicity regions. Timoshenko beam model is used to simulate a building with vertical irregularity. In-situ dynamic tests of buildings are compiled to delimit the model inputs. Design charts correlating drifts and shear area ratios to periods are developed. Drift demands are not critical for high-rise buildings. Abstract: In low-to-moderate seismicity regions, the limited seismic displacement demands could probably render tall buildings remaining nearly elastic during a maximum considered earthquake. Previous studies have shown the capability of the uniform Timoshenko beam model in resembling the dynamic behaviors of regular buildings. This article describes response spectrum analyses on the non-uniform Timoshenko beam model, considering the first four vibration modes to assess the seismic demands on various building types, which encompass low-rise wall or frame buildings and high-rise shear wall buildings with or without transfer structures. Simplified design charts correlating the global seismic demands – spectral accelerations, maximum interstory drift ratios, roof drift ratios and required shear areas – to the fundamental translational period of each building are developed. The structural periods could be determined from in-situ dynamic tests, full frame models or an appropriate period-height equation, the latter of which is provided here by calibrating from in-situ vibration tests of regional buildings constructed in compliance with British Standards. This simplified approach provides a fast track to seismic performance for both existing and new buildings, which could easily be comprehended by engineers without prior knowledge of seismic design.